MENINGKATKAN HASIL BELAJAR AKUNTANSI DENGAN PENERAPAN METODE PEMBELAJARAN BERBALIK (RECIPROCAL TEACHING) PADA KOMPETENSI DASAR MENYUSUN NERACA LAJUR PERUSAHAAN DAGANG SISWA SMK PGRI 2 NGANJUK - Widyastuti, Lely Farida (CV Sintesia, 2024)
Thus, the obtained data shows that the implementation of reciprocal teaching method is able to increase students’ enthusiasm and learning success in basic competence of creating companies’ working sheet at XI.111.3 class of SMK PGRI 2 Nganjuk. Based on the result of the research, the researcher suggests several things as follows: 1) Teachers should manage their time carefully when implementing reciprocal teaching method because it is time- consuming. Even though students tend to be dominant during teaching and learning processes, teachers should always be the most main facilitators. 2) Reciprocal teaching method should be practiced and developed well as one of alternative ways in teaching accounting to increase students’ enthusiasm and learning success. Increasing students’ ability in learning basic competence of creating companies’ working sheet by implementing Reciprocal Teaching Method at XI.111.3 class of SMK PGRI 2 Nganjuk in the academic year of 2019-202. Some internal and external factors determine students’ accomplishment in achieving learning success standards. Internal factors, which emerge from students’ awareness, plays an important role in determining learning success. While, external factors, which support students’ learning success can come from family’s atmosphere, school environment, and another wider society. This research discusses one of those external factors, that is, a teaching method that comes from school environment. Researcher implements reciprocal teaching method during teaching and learning processes. The method gives students a chance to obtain intra-group guidance and cooperate in understanding teaching materials and to gain students’ self-understanding. The statement of the problem in this research is how are the XI.111.3 students of SMK PGRI 2 Nganjuk’s activities and the result of their study during and after learning to create companies’ working sheet with reciprocal teaching method? This research uses quantitative and qualitative data analysis. Learning success is 0% at the stage of pre-cycle. While at the first cycle, learning success is 32%. The average score of the teacher’ capability in managing the class is 4.5. The students’ enthusiasm of individual learning is 3.8. While their enthusiasm of group learning is 4.8. In the second cycle, learning success is at 32%. The average score of the teacher’ capability in managing the class is 6.4. The students’ enthusiasm of individual learning is 4.9. While, their enthusiasm of group learning is 5.25.